2015
DOI: 10.1002/2014jf003330
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of a two‐dimensional brittle granular column: Implications for understanding dynamic rock fragmentation in a landslide

Abstract: International audienceWe investigate numerically the failure, collapse, and flow of a two-dimensional brittlegranular column over a horizontal surface. In our discrete element simulations, we consider a verticalmonolayer of spherical particles that are initially held together by tensile bonds, which can be irreversiblybroken during the collapse. This leads to dynamic fragmentation within the material during the flow.Compared to what happens in the case of a noncohesive granular column, the deposit is much roug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 87 publications
(129 reference statements)
5
33
0
Order By: Relevance
“…Therefore, we chose a more reasonable method to determine the degree of fragmentation. The relative breakage ratio ( B r ), which has recently been widely used (Bowman et al, 2012; Hardin, 1985; Langlois et al, 2015), is applied to describe the degree of fragmentation in each experiment. The detailed method of calculating the relative breakage ratio is described in section 2.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we chose a more reasonable method to determine the degree of fragmentation. The relative breakage ratio ( B r ), which has recently been widely used (Bowman et al, 2012; Hardin, 1985; Langlois et al, 2015), is applied to describe the degree of fragmentation in each experiment. The detailed method of calculating the relative breakage ratio is described in section 2.…”
Section: Resultsmentioning
confidence: 99%
“…In this figure, FSDs from each experiment are calculated using 15 bins, and an average FSD is achieved by averaging each bin for experiments with the same initial conditions. In Figure 5b the inverse of the characteristic fragment mass, m c , is plotted against the breakage parameter, Φ, used in previous studies [e.g., Bowman et al, 2012;Langlois et al, 2015]. The breakage is defined as…”
Section: Observationsmentioning
confidence: 99%
“…Important exceptions are the experiments of Bowman et al [], which showed that samples could accelerate after fragmentation, causing the front of their deposits to travel further the more fragmentation they experience. Similar results were also shown in numerical models by Langlois et al []. While these are illuminating studies of the kinematics of fragmenting rockslides, in order to study the energy budget of the system, one would need to consider the travel length of the center of mass rather than the front.…”
Section: Introductionmentioning
confidence: 99%
“…Balmforth and Kerswell () have analyzed and compared the experimental and constitutive theoretical results of the granular column collapse. Numerical studies of column collapse of granular mixtures have been concentrated on the effects of the initial column geometry (Utili et al, ; Zenit, ), the input parameters (Cleary & Frank, ; Kermani et al, ; Staron & Hinch, , ), the particle shape (Tapia‐McClung & Zenit, ), and grain fragmentation (Langlois et al, ) on the kinematic characteristics of granular flows. These studies demonstrate that the mobility of granular flows depends not only on the material volume involved but also on the initial column geometry and other factors affecting the rheological properties of granular flows.…”
Section: Introductionmentioning
confidence: 99%
“…These granular flows are among the most dangerous natural disasters and can cause extensive damages to the engineering structures because of their powerful ability to move freely from their sources and destructive impact energy (Aaron & Hungr, 2016;Robinson et al, 2015). Various mechanisms have been proposed to explain the extremely large flow mobility that particle flows exhibit, such as entrapped air fluidization (Kent, 1966), air cushion theory (Shreve, 1968), dust dispersion fluidization (Hsü, 1975), fluidization caused by acoustic energy (Collins & Melosh, 2003;Melosh, 1979), lubrication by liquefied saturated soil (Hungr & Evans, 2004), size segregation (Iverson et al, 2010;Roche et al, 2011), self-lubrication by molten rock at the base (De Blasio & Elverhøi, 2008;Goren & Aharonov, 2007), and dynamic rock fragmentation (Davies et al, 2010;Langlois et al, 2015). However, numerical investigations from the particle scale perspective to verify these assumptions and theories have yet to be fully conducted.…”
Section: Introductionmentioning
confidence: 99%